2017
DOI: 10.1038/s41467-017-00041-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ultrafine particle levels in São Paulo’s atmosphere during shifts from gasoline to ethanol use

Abstract: Despite ethanol’s penetration into urban transportation, observational evidence quantifying the consequence for the atmospheric particulate burden during actual, not hypothetical, fuel-fleet shifts, has been lacking. Here we analyze aerosol, meteorological, traffic, and consumer behavior data and find, empirically, that ambient number concentrations of 7–100-nm diameter particles rise by one-third during the morning commute when higher ethanol prices induce 2 million drivers in the real-world megacity of São P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 60 publications
(98 reference statements)
2
18
0
1
Order By: Relevance
“…3 ). The significant contribution of LDV to aerosol number concentration obtained here corroborates a recent study, which has observed a significant effect on UFP in a background sampling site in SPMA associated to the ethanol content used by passenger vehicles 36 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…3 ). The significant contribution of LDV to aerosol number concentration obtained here corroborates a recent study, which has observed a significant effect on UFP in a background sampling site in SPMA associated to the ethanol content used by passenger vehicles 36 .…”
Section: Resultssupporting
confidence: 91%
“…Salvo et al . 36 ). Conversely, a limitation of the methodology proposed here is to force species of interest to be described by the four PMF factors (lacking, for example, an industry factor as predictor).…”
Section: Resultsmentioning
confidence: 99%
“…O uso de etanol em automóveis, comum em países como Brasil, EUA e Suécia, é capaz de reduzir as emissões de poluentes e de material particulado (diâmetro < 50 nm) quando comparado à gasolina e óleo diesel, bem como aumentar a concentração de ozônio com implicações diretas a saúde e mudanças climáticas (SALVO et al, 2017). Alguns modelos comerciais de tratores agrícolas apresentam configurações de economia de combustível em comparação com a operação regular; no entanto, as emissões (ex: CO, CO2, NOx e Hidrocarbonetos) são maiores para condições de relação potência/torque elevadas na configuração econômica (SCHLOSSER et al, 2017).…”
Section: Introductionunclassified
“…Biofuels such as bioethanol are becoming increasingly important due to their ability to reduce fossil fuel consumption and reduce greenhouse gas and pollutant emissions (Goldemberg, 2007;Salvo et al, 2017). Large-scale biofuel production benefits greatly from hightemperature fermentation (≥ 40°C) which significantly reduces cooling costs and helps prevent contamination (Abdel-Banat et al, 2010;Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%